2018
DOI: 10.1002/path.5034
|View full text |Cite
|
Sign up to set email alerts
|

The rise of a novel classification system for endometrial carcinoma; integration of molecular subclasses

Abstract: Endometrial cancer is a clinically heterogeneous disease and it is becoming increasingly clear that this heterogeneity may be a function of the diversity of the underlying molecular alterations. Recent large-scale genomic studies have revealed that endometrial cancer can be divided into at least four distinct molecular subtypes, with well-described underlying genomic aberrations. These subtypes can be reliably delineated and carry significant prognostic as well as predictive information; embracing and incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
169
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(170 citation statements)
references
References 102 publications
0
169
0
1
Order By: Relevance
“…We also discuss how the integrated molecular entities may provide clues to specific targeted treatment modalities that can be exploited in advanced‐stage or recurrent disease. For a more detailed background on the molecular EC classification, as well as assays that may be used for the diagnosis, the reader is referred to other reviews …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also discuss how the integrated molecular entities may provide clues to specific targeted treatment modalities that can be exploited in advanced‐stage or recurrent disease. For a more detailed background on the molecular EC classification, as well as assays that may be used for the diagnosis, the reader is referred to other reviews …”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed background on the molecular EC classification, as well as assays that may be used for the diagnosis, the reader is referred to other reviews. [15][16][17] Endometrioid Endometrial Carcinoma (EEC),…”
Section: Introductionmentioning
confidence: 99%
“…For many cancers, these efforts have led to new, integrated classifications in which genomic and histological features often align in a striking and highly informative fashion. This is exemplified in the present Annual Review Issue (ARI) by updates on the classification of renal cell carcinoma (Hsieh et al ) and endometrial carcinoma (McAlpine et al ). Conversely, in addition to uncovering novel and highly relevant subtypes of many cancers, these studies have also revealed robust and biologically plausible commonalities between cancers arising in different organs, as shown by the comparison of clear cell carcinomas of the ovary and kidney by Ji et al .…”
mentioning
confidence: 97%
“…The prognostic value of TCGA in EC has been corroborated in large cohorts included in studies developed by the Vancouver and PORTEC (Post Operative Radiation Therapy in Endometrial Carcinoma) groups [5,6]. This can be especially relevant in adjuvant treatment choices for high to intermediate-risk EC patients that are likely to be impacted by the integrated molecular classification [7], while recurrent disease may continue to represent an additional challenge. Despite these stratification conditionings, and as demonstrated in the majority of solid tumours, EC shows intratumour heterogeneity with different neoplastic cell components within the same tumour.…”
Section: Challenges In Endometrial Cancermentioning
confidence: 97%